2012
DOI: 10.1103/physrevlett.109.120402
|View full text |Cite
|
Sign up to set email alerts
|

All Entangled Pure States Violate a Single Bell’s Inequality

Abstract: We show that a single Bell's inequality with two dichotomic observables for each observer, which originates from Hardy's nonlocality proof without inequalities, is violated by all entangled pure states of a given number of particles, each of which may have a different number of energy levels. Thus Gisin's theorem is proved in its most general form from which it follows that for pure states Bell's nonlocality and quantum entanglement are equivalent.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
83
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 19 publications
1
83
0
Order By: Relevance
“…We note that our result above strengthens previous works [21,22] in two folds. On the one hand all pure multipartite entangled symmetric states are proved to exhibit genuine multipartite nonlocality and on the other hand, this nonlocality can be revealed by a test without inequality.…”
supporting
confidence: 92%
See 2 more Smart Citations
“…We note that our result above strengthens previous works [21,22] in two folds. On the one hand all pure multipartite entangled symmetric states are proved to exhibit genuine multipartite nonlocality and on the other hand, this nonlocality can be revealed by a test without inequality.…”
supporting
confidence: 92%
“…Discussions.-All pure entangled states exhibit standard nonlocality [21,23] and it is an open problem whether all pure genuine multipartite entangled states are genuine multipartite nonlocal [2]. We have made a progress towards solving this problem by proposing a test without inequality, with the help of which we have shown that all entangled symmetric states are genuine multipartite nonlocal.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…If this new Majorana point is not one of the Majorana points of |ψ , condition (6) is satisfied automatically. It has been proven [6] that for all symmetric states except Dicke states, there exists a choice of |η i such that (6) to (8) are all satisfied, which also violates (9). Although Dicke states do not satisfy (6) to (8), it is also possible to choose measurement settings such that they violate (9) in a 2-setting/2-outcome experiment [6].…”
Section: N-party Hardy Paradox and Inequalitymentioning
confidence: 99%
“…Although Dicke states do not satisfy (6) to (8), it is also possible to choose measurement settings such that they violate (9) in a 2-setting/2-outcome experiment [6]. Indeed, is has recently been shown that all pure entangled states violate (9) [9].…”
Section: N-party Hardy Paradox and Inequalitymentioning
confidence: 99%